Praktik Kepemimpinan Kepala Sekolah dalam Mengelola Kinerja dan Profesionalisme Guru Sekolah Dasar: Studi Kasus Kualitatif - Ayumi Vesaka; Santi Eka Putri; Elliza Nofri Yenny; Yetty Morelent; Erwinsyah Satria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe and analyze the principal’s leadership practices in managing teachers at the elementary school level, particularly civil servant teachers (ASN) and school education personnel (TKS). The study employed a qualitative approach with a case study design to gain an in-depth understanding of the principal’s leadership practices at SDN 126/VI Muara Jernih. Data were collected through semi-structured interviews, non-participant observations, and documentation related to school activities and teacher management. Data were analyzed descriptively through data reduction, data display, and conclusion drawing and verification.The findings reveal that the principal applies a democratic leadership style characterized by openness to teachers’ input, decision-making through deliberation, firmness in enforcing rules, and open two-way communication. The management of ASN and TKS teachers is conducted fairly and proportionally based on each teacher’s competence, experience, and capability. Furthermore, the principal consistently provides guidance and supervision to support teachers’ professional development. This leadership practice has a positive impact on teachers’ performance, discipline, and motivation, while also fostering a harmonious and conducive work climate within the school.This study contributes to the development of effective, fair, and inclusive school leadership practices in managing teachers at the elementary school level.